Impulse transformer based secondary-side self-powered gate-driver for wide-range PWM operation of SiC power MOSFETs - Garcia, Jorge; Gurpinar, Emre; Castellazzi, Alberto (2016)
This work proposes a solution for an isolated gate driver for SiC MOSFETs, based on a magnetic transformer that simultaneously provides to the secondary side the turn-on and turn-off gate signals and the power required for an adequate gate control. This avoids the use of a dedicated DC-DC isolated converter and optocoupler. The original pulse signal is converted into impulses, avoiding transformer saturation at any duty ratio operation. The small size of the resulting transformer enables an overall size reduction vs. conventional solutions (based either in magnetic or optocoupler + power supply). This enables much more compact designs, which are critical in high-power density applications and multilevel converters. After describing the basic operation of the driver, experimental results on a 2kW prototype demonstrate the feasibility of the proposal. It is worth mentioning that this design is also suitable for GaN devices with minor design changes